Beam Shaping Technique for 5-mm Fiber-coupled Laser Diode Bars with Lens Group - Jawad , Hind J (Iraqi Journal of Science, 2023)
In the last few years, fiber-coupled diode lasers have shown massive applications in many fields of communication and scientific research. Particularly, the pumping of solid-state lasers is a key application for more powerful diode lasers enabling good solutions in various laser micro methods like metal cutting, sintering, structuring as well as drilling. In this work, a simple beam shaping method is demonstrated for coupling a high-power semiconductor laser diode into multi-mode fiber optic using optical lenses. The optical lenses as beam transformation components are utilized to reshape the asymmetrical irradiation of the diode laser bar and to circularize the laser beam. Using this simple method, compact, high-output-power, and high-brightness fiber-coupled laser diode systems are achieved. The obtained results show that the entire optical coupling efficiency of the system is more than 65%.